2012
DOI: 10.1557/opl.2012.274
|View full text |Cite
|
Sign up to set email alerts
|

Modified Polylactide Microfiber Scaffolds for Tissue Engineering

Abstract: Physical properties of porous membranes made of biocompatible and biodegradable polymers have been studied. The membranes are intended to be used as scaffolds for the regeneration of soft and hard tissues. Polylactides, polycaprolactone and some of their derivates are biocompatible as well as biodegradable materials, and are used for the preparation of nanofibers and nanoporous membranes. These membranes also have comparative advantages as cellular scaffolds for tissue engineering since they can be prepared to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 6 publications
1
6
0
2
Order By: Relevance
“…Both of the bacterial assays shows that all PLLA/PLLA-g-HA and PLLA/HA scaffolds are excellent substrates that enable efficient bacterial cell adhesion. The results are in accordance with the good bioadhesive properties for eukaryotic cells previously observed [14]. We can resume that to promote bacterial adhesion the substrate need to be hydrophobic, and for cellular protein adhesion the substrate has to be hydrophilic.…”
Section: Bacterial Adhesionsupporting
confidence: 91%
See 2 more Smart Citations
“…Both of the bacterial assays shows that all PLLA/PLLA-g-HA and PLLA/HA scaffolds are excellent substrates that enable efficient bacterial cell adhesion. The results are in accordance with the good bioadhesive properties for eukaryotic cells previously observed [14]. We can resume that to promote bacterial adhesion the substrate need to be hydrophobic, and for cellular protein adhesion the substrate has to be hydrophilic.…”
Section: Bacterial Adhesionsupporting
confidence: 91%
“…In the scaffolds under our study no preferential position tendency of the cells onto the scaffold fibers was observed suggesting that the cell morphology is independent of the topography of the fibers. This observation is relevant because roughness may lead to the morphology and position of the cells in a scaffold [14].…”
Section: Mtt Assay and Neutral Red Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…Las soluciones de PLA fueron preparadas según la metodología usada por Vera et al [12] Tratamiento post electrohilado Con el fin de mejorar las propiedades estructurales y mecánicas de las fibras, estas fueron sometidas a un proceso de calentamiento a 80 ºC durante 10 horas. La temperatura de este proceso fue dada de acuerdo a la temperatura de transición vítrea del polímero (Tg = 60 ºC), con lo cual se asegura un cambio en la estructura interna del polímero.…”
Section: Electrohiladounclassified
“…Key words: Poly Lactic Acid, electrospinning, nanofibers, crystallinity, mechanic properties. para la regeneración dental, utilizando la técnica de electrohilado [12]. Se obtuvieron andamios de PLA mezclado e injertado con nano partículas de hidroxiapatita.…”
Section: Introductionunclassified